MODEL KEBUTUHAN PENUMPANG BANDAR UDARA DI INDONESIA - Pada Lumba; Arie Syahruddin, Sabarani (Universitas Pasir Pengaraian, 2013)
Based on data from Statistics Indonesia from 1999 to 2010, where the number of passenger airports in Indonesia is likely to increase. This increase in the number of passengers when not accompanied by an increase in airport facilities would have caused problems in the next few years, mainly related to the comfortable of passengers at the airport.For that analysis needs to be done to get the models arrival and departure passengers at the existing condition. Independent variables used in this study is a population (X1), PDRB (X2), hotel occupancy (X3), the number of foreign tourists (X4), PMDN (X5), PMA (X6), the number of students (X7), number of lecturer (X8), exports (X9), import (X10), the number of large construction companies (X11), the number of workers (X12).